Pengetahuan, Asupan Energy dan Zat Gizi Berhubungan dengan Kekurangan Energy Kronis pada Wanita Prakonsepsi - Hubu, Novika; Nuryani, Nuryani; Hano, Yanti Hz (Gorontalo Journal of Public Health, 2018)
Choronic energy malnutrition is health problems in women reproductiveage. The purpose of this study was assessed association betweennutrition knowledge, energy and protein intake with chronic energymalnutrition. Design study was observational study with cross sectionaldesign. The Sample were taken by exshautive sampling with collected152 praconseption women. Study was conducted in Boalemo regency.Data analysis using univariate and bivariate analysis which was chisquare test. The result showed that there were only 2,6% in age lessthan 20 years, most of educational level les than nine years 66,4%,92,8% had occupation as house wife, 28,8 % choronic energymalnutrition, 52,6% low nutrition knowledge, 55,9% low energy intakeand 54,6% low protein intake. Bivariate analysis showed women whohad CEM with low nutrition knowledge 51,3% higher than high level ofnutrition knowledge 2,7%, low penergy intake 37,6% higher thanadequate energy intake 16,4%, low protein intake 36,1% higher thanadequate protein intake 18,8%. Chi square test showed there wereassociation between nutrition knowledge (p = 0,000), energy intake (p =0,007) and protein intake (p = 0,029) with chronic energy malnutrition inpraconseption women. It was concluded tha low nutrition knowledge,low energy and protein intake had association with chronic energymalnutrion.